Convergence of External Crohn’s Disease Risk Factors on Intestinal Bacteria - Oberc, Alexander; Coombes, Brian K. (Frontiers in Immunology, 2015)
Crohn’s disease (CD) is an immune-mediated intestinal illness that significantly compromises health in many developed countries. Although definitive causes remain elusive, the required contribution of microbes in the progression of disease has become an accepted concept. Known CD risk factors such as antibiotic use and acute infectious gastroenteritis may impact the gut. This concept is now being explored with a view towards understanding the beneficial and unfavorable microbes that may be altered in numbers during such external insults. A comprehensive understanding of the microbial component to CD could be useful clinically as future therapies may focus on preventing risk exposures on susceptible individuals, eliminating harmful microbes, or restoring a protective gut microbiome. Here, we examine how acute infectious gastroenteritis and antibiotic exposure may impact the gut microbiota in the context of inflammation in CD.